A Novel β-Thalassemia Insertion/Frameshift Mutation Between Codons 77/78 (p.Leu78Profs*13 or HBB: c.235_236insC) Observed in a Family in Bangladesh. (2nd November 2017) - Aziz, Abdul; Das, Sudipta A.; Khan, Waqar A.; Sadiya, Salma; Banu, Bilquis; Sarwardi, Golam; Luna, Rowshon Z.
Abstract: β-Thalassemia (β-thal) is one of the most common inherited hemoglobin (Hb) disorders, worldwide. A 28-year-old female and her husband came to Dhaka Shishu (Children) Hospital, Bangladesh for prenatal diagnosis for thalassemia mutations. We identified and characterized a novel β-thalassemia (β-thal) mutation due to an insertion of cytosine between codons 77 and 78 (p.Leu78Profs*13) found in mother in a heterozygous state. This mutation caused an insertion in the normal reading frame of the β-globin coding sequence and the new stop codon being the amino acid 90 ( HBB : c.235_236insC) in exon 2 that leads to a β 0 -thal phenotype.